Pengaruh Komunitas Merek (Brand Community) dan Personalitas Merek (Brand Personality) terhadap Loyalitas Merek Oriflame di Kota Padang - Yasri, Yasri; Rahmiati, Rahmiati; Sylvia, Devi (Jurnal Kajian Manajemen Bisnis, 2014)
The objective of this research is to analyze influence of brand community and brand personality to customer layalty of Oriflame in Padang city. The population of this research is all of members of Oriflame community in Padang city. Sample size is 100 persons. Sample technique is sampleÂ  random sampling. The data has collected are primery and scondary data. The data collected by questionaire andÂ  documentation. Data are analyzed with multiple regression. The research results revealed that (1) brand community has positive and significant influence to Oriflame brand loyalty in Padang city (2) brand personality has positive and significant influences to Oriflame brand loyalty in Padang city. The brand community has biggest influences than brand personality